Fracture properties of concrete under freeze–thaw cycles and sulfate attack. (3rd October 2022) - Hu, Shaowei; Yin, Yangyang
Highlights: The fracture properties of concrete exposed to freeze–thaw cycles in different sulfate solutions were investigated. The visual change, weight loss, relative dynamic elastic modulus, compressive strength and fracture parameters of concrete were studied. The evolutions of the fracture process zone and damage scale of the specimens were analyzed. Abstract: The fracture properties of concrete exposed to freeze–thaw (F-T) cycles in different sulfate solutions were investigated using pre-notched three-point bending beams. 5 % Na2 S04, 5 % MgS04 (by mass) and water, i.e. three exposure conditions were considered. The visual change, weight loss, relative dynamic elastic modulus, compressive strength and fracture parameters of concrete were measured at every 25F-T cycles. The evolutions of the fracture process zone (FPZ) and damage scale of the specimens were studied. Results indicate that (1) before 100F-T cycles, the specimens in water suffer severer damage than those in sulfate solutions, and the deterioration degree of the specimens in 5 % Na2 S04 is the greatest after 200F-T cycles. (2) With increasing the F-T cycles, the obtained double- K fracture parameters, microcracking zone length and aggregate occlusion zone decrease linearly. Morever, the maximum FPZ length basically decreases, and a small increase tendency is observed at 125 and 150F-T cycles due to the significant increase in the deformation capacity of the specimens.